ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI KEPUASAN NASABAH DANA PENDIDIKAN PADA PT ASURANSI TAKAFUL KELUARGA DI KOTA MEDAN - Yenni Samri Nasution (AT-TAWASSUTH: Jurnal Ekonomi Islam, 2019)
This research will answer about the factors that influence takaful education fund customers at PT. Medan City Family Takaful Insurance. This research is a quantitative study, using 70 samples and obtaining data using a questionnaire with a Likert scale data processed using the SPSS application. The results showed that the product variables affect customer satisfaction takaful insurance. This can be seen from the test results of 2.46379> t table 1.66827. The promotion variable does not affect the satisfaction of takaful insurance customers. This can be seen from the results of the tcount 1.09880> t table 1.66827. Service variables affect customer satisfaction takaful insurance. This happens because the education fund takaful insurance product has tried to provide excellent service in accordance with customer needs. This can be seen from the results of the t-test 3.427700> t table 1.66827. Free variables (products, promotions and services) simultaneously affect the satisfaction of education takaful insurance fund customers.